Dispossession of the Debtor Within the Scope of Qatari Civil Law: A Comparative Study - Juma, Abdul Rahman (Dirasat: Shari'a and Law Sciences, 2020)
This research aims to examine the role of different Arab legislations in addressing the issue of stripping the debtor within the scope of the Qatari civil law. Since there is no Qatari juristic research that deals with the sponsorship contract in general, this research discusses this issue in particular. The research discusses the time when the guarantor has to hold on to the payment in the abstraction and the time when the waiver of this payment by the guarantor falls. This research is based on a comparative analytical approach. The study reached a number of results, including: the payment by stripping the debtor's funds before execution on the guarantor's funds is limited to the personal guarantor, the legal, judicial or commercial guarantor is prohibited from adhering to this payment, as they are joint guarantors, that the payment by stripping until it is considered acceptable, the guarantor must guide the creditor at his expense to the debtor's funds to fulfill the entire debt. The debtor's money, to which the creditor has been directed, is equated to be movable or real estate. The study recommended the need to develop judicial systems in accordance with the doctrinal and legal developments related to administrative contracts. The two researchers also recommended that the research and academic studies centers take care of modern topics that develop according to economic developments, and edit the doctrinal and legal consideration of them in accordance with the requirements of economic development and technical development.